Zoneamento geoambiental da bacia hidrográfica do Rio São João (MG) como subsídio à gestão dos recursos hídricos - Jacó, Ana Paula (2019)
Considering the importance of the preservation and sustainable use of water resources nowadays, in the face of accelerated social and economic development, this work represents an important tool of direct contribution in the environmental and water resources management of the São João River Watershed (BH-SJ), which presents a drainage area of 2,417.7 km² and is located in the southwest of the state of Minas Gerais, Brazil. This basin is characterized by its diversity and intensity of anthropic interventions, which affect (directly or indirectly) its water regime. The geo-environmental investigation, associated to zoning techniques, stands out as an essential tool to subsidize planning and management of land-use. In this context, using Geo-environmental Zoning (ZG) techniques and data cross checking, this work sought to elaborate and interpretative cartographic documents as a form of subsidy to the territorial planning and management of the water resources of BH-SJ, based on an integrated diagnosis of its water availability and demand. Among the cartographic documents elaborated, the following stand out as the main ones: Letter of Surface Water Availability; Letters of Surface and Subterranean Water Demand; Letter of Punctual Anthropogenic Actions and the Geo-environmental Zoning Charter for the BH-SJ Water Stress Potential. These documents were elaborated in a scale of 1: 50,000 in the GIS environment (Geographic Information Systems) from the mapping and crossing of intermediate data classified as geo-environmental attributes. The results obtained in the Letters of Water Availability and Demand show the features of BH-SJ that present the largest and the smallest occurrences of these two components, highlighting the areas according to their priority levels. Similar terms were used to classify the occurrence of the components: Very Low, Low, Medium, High and Very High. The Letter of Punctual Anthropogenic Actions illustrates that the consumptive uses of water resources in the watershed can go well beyond the estimated values due to the intensity of occurrence and the deficiency in the user registry by the competent bodies. The ZG Chart on Water Stress Potential was elaborated from the intersection between the water availability and demand results. From the subdivision of the study area in Microbasins (Mbs), the diagnosis of water stress potential in 581 Mbs was obtained and presented the following classification: Very Low (17Mbs); Low (344 Mbs); Medium (146 Mbs); High (70 Mbs); Very High (4 Mbs). The Mbs classified with high and very high potential of water stress are characterized by the high index of anthropogenic interventions in their water resources, in this way they fall into the class of high priority for measures that aim to improve the management of use in these places. Therefore, the results of this research represent an effective tool to subsidize the decision management and support, considering the feasibility of integrated analysis of the territory of BH-SJ, aiming at the sustainable use of water resources and the prevention or mitigation of possible conflicts of use in the areas that present the greatest potential to the water stress generated by the excessive use of this resource.